Nutritive value of perennial pastures along an elevation gradient in tropical conditions - Villalobos, Luis; Arndt, Claudia; Van Der Hoek, Rein; Mazzetto, Andre M.; Chadwick, Dave (FRONTIERS MEDIA, 2025)
The nutritive value of forages is one of the main drivers of productivity for livestock. In many tropical regions, same grass species occur at different elevations, but few studies have evaluated nutritive value changes within elevation gradients. Methods The objective of this study was to analyze the changes in nutritive value of six grass genera across and within elevation gradients in Costa Rica. We synthesized elevation and nutritive data for crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), and in-vitro dry matter digestibility (IVDMD) in a database ( n = 1,192) containing five C 4 grasses ( Urochloa , Cynodon , Digitaria , Megathyrsus , and Cenchrus ) and one C 3 grass ( Lolium ). Urochloa , Megathyrsus , and Digitaria are grasses grown primarily at low elevation (0–999 masl), and Lolium at high elevation (>2,000 masl). Results Cynodon and Cenchrus overlap low to mid, and mid to high elevations, respectively. Greater CP and lower NDF concentrations were found for grasses grown at high elevation compared to those grown at low elevation (CP = 18.2–22.4 vs. 7.8–15.2%, NDF = 48.9–49.3 vs. 64.6–67.3%, and ADF = 32.2–33.2 vs. 37.4–44.3%). Consequently, IVDMD was greater for grasses grown at high than at low elevation (80.9–86.0 vs. 61.4–71.1% of DM). CP increased with elevation, especially for Lolium , while NDF and ADF tended to decrease for Megathyrsus , Urochloa , and Cenchrus . Discussion The groups of grasses classified by nutritive value in this study, provide a baseline for potential nutrient supply to livestock and rations adjustments accordingly.